The effect of increasing the water content on rocks characteristics from Şuior, Romania - Toderas, M.; Moraru, R. (Розробка родовищ, 2017)
Findings. Some of the mining works with straight walled profiles, vaulted ceiling and unsupported floor were executed in rocks with pronounced trends towards deterioration and swelling of floors; given that, the rocks contain insertions of kaolin andesite, have shown a tendency to swelling of floor, which required the use of circular profiles and horseshoe-shaped profiles with enclosed floor. Observations have highlighted that the deformations of the floor are not due only to the fact that the works are located in rocks with low resistance, but also because the water is accumulated in the floor of these works, changing in a short time the mechanical properties of the rocks. Swelling of the floor is the consequence of intensive water-rock action, having the effect of misalignment of the floor, destructive effect upon the foundation and of support base, this attempt a horizontal displacement towards the interior of the gallery, unbalancing the support.